2022
DOI: 10.1007/s00406-021-01377-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of ketamine on the pregenual anterior cingulate: linking spontaneous activation, functional connectivity, and glutamate metabolism

Abstract: Ketamine exerts its rapid antidepressant effects via modulation of the glutamatergic system. While numerous imaging studies have investigated the effects of ketamine on a functional macroscopic brain level, it remains unclear how altered glutamate metabolism and changes in brain function are linked. To shed light on this topic we here conducted a multimodal imaging study in healthy volunteers (N = 23) using resting state fMRI and proton (1H) magnetic resonance spectroscopy (MRS) to investigate linkage between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…During infusion, on the neurometabolic level, no glutamatergic changes were observed, as expected for the investigated region. The lack of immediate glutamatergic modulation is consistent with a recent study that did not find significant changes in Glu, Gln, or Gln/Glu ratio in the pgACC during S-ketamine infusion [38]. This may be due to a very transient increase in Glu that was not captured by our measurement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…During infusion, on the neurometabolic level, no glutamatergic changes were observed, as expected for the investigated region. The lack of immediate glutamatergic modulation is consistent with a recent study that did not find significant changes in Glu, Gln, or Gln/Glu ratio in the pgACC during S-ketamine infusion [38]. This may be due to a very transient increase in Glu that was not captured by our measurement.…”
Section: Discussionsupporting
confidence: 92%
“…Healthy participants were therefore chosen to allow for investigations without confounding effects of an antidepressant treatment. Furthermore, since both immediate [37,38] and delayed [28,29] brain changes in healthy participants have been already reported in the literature, we expected to observe the hypothesized relationship also in healthy participants. Indeed, a previous study performed in healthy participants showed the association between the effects 1 h and 24 h after infusion [28].…”
Section: Materials and Methods Study Design And Participantsmentioning
confidence: 57%
See 1 more Smart Citation
“…Notably, the change from baseline in Glx over the entire infusion period was not significantly different between treatment groups. Gärtner et al (2022) reported a trend increase in Glu, but no changes in Gln or Gln/Glu 25 min after esketamine infusion compared to a baseline session (∼0.4 mg/kg) in 17 participants.…”
Section: Resultsmentioning
confidence: 82%
“… Racemic ketamine 0.5 mg/kg n.s. 24 h post- infusion 7 T PRESS pgACC 20 × 20 × 20 Glu, Gln In-house linear combination program = Glu from baseline to post-administration = Gln between baseline and post-administration Gärtner et al (2022) HC N = 16 open-label pre-post design without placebo i.v. Es-ketamine 0.12 mg/kg + 0.25 mg/kg/h n.s.…”
Section: Resultsmentioning
confidence: 99%